2007
DOI: 10.1007/s00404-007-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

Control of presacral venous bleeding, using thumbtacks

Abstract: Use of thumbtacks in such patients is simple, cost effective and life saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Previous studies have consistently reported that gastrointestinal complications, such as small bowel obstruction, ileus, or defecation disorders occur in approximately 0.1 to 5% of sacrocolpopexy procedures. The mesh placed between the sacrum and vagina (cervix) always narrows the pelvis, and the cause of the defecation disorders may be reduced space in the pelvis (outlet obstruction), adhesions, or trauma of the hypogastric nerves ( 5 , 7 , 9 11 ). However, presacral hemorrhage is the most worrying intraoperative complication of sacrocolpopexy, and may have life-threatening consequences ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have consistently reported that gastrointestinal complications, such as small bowel obstruction, ileus, or defecation disorders occur in approximately 0.1 to 5% of sacrocolpopexy procedures. The mesh placed between the sacrum and vagina (cervix) always narrows the pelvis, and the cause of the defecation disorders may be reduced space in the pelvis (outlet obstruction), adhesions, or trauma of the hypogastric nerves ( 5 , 7 , 9 11 ). However, presacral hemorrhage is the most worrying intraoperative complication of sacrocolpopexy, and may have life-threatening consequences ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, their implementation has been the subject of multiple communications, most of which reported good results[35-40]. However, pin placement can be technically difficult[22,37], especially in narrow pelvises[41], when the contour of the sacrum is not sufficiently smooth and regular or when osteoporotic disease is present in the bone[29,42].…”
Section: Resultsmentioning
confidence: 99%
“…This rule is applicable to presacral venous haemorrhage. Conventionally, there are several ways used to achieve haemostasis such as cautery, suture ligation, hot packs, ligation of internal iliac artery, and application of absorbable gelatin sponge or microfibrillar collagen (Ayuste E, 2004 andKumar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%